A community-based study on the awareness and prevention of hypercholesterolemia in adults - Bhatia, Kunalika; Patel, Puja T.; Das, Biplob K. (International Journal Of Community Medicine And Public Health, 2021)
Background: Intake of unhealthy junk food results into long standing health issues and the research in this paper is focused towards analyzing the knowledge of non-medical population about hypercholesterolemia and to upgrade their education concerned with healthy lifestyle modifications and essential safety measures identified with elevated cholesterol levels and related diseases. Methods: It was a prospective pre-and post-education interventional study carried out on 400 non-medical students at PES degree college Bangalore. A self-managed survey was conveyed to participants using a validated questionnaire during their usual college hours. The data analysis was done utilizing Microsoft excel tool. Results: Out of 400 participants in pre-education interventional study awareness about hypercholesterolemia was found excellent in 129 subjects, average in 243 subjects and poor in 28 subjects, where as in post-education interventional study awareness about hypercholesterolemia was found to be excellent in 355 subjects average in 44 subjects and poor in 1 subject. Conclusions: The significant increment was found in the degree of information among the participants. All over the study was an achievement and the objective of the examination was satisfied. Few participants showed lack of interest however spreading awareness and instructing about wellbeing viewpoints can bring the distinction just if the picked-up information is executed in everyday life.